A Holistic Management Model of Islamic Religious Education Based on Spiritual, Emotional, and Intellectual Intelligence - Iim Al Imron; Fitri Hilmiyati; Yahdinil Firda Nadirah; Fandy Adpen Lazzavietamsi; Aas Siti Sholichah Sholichah (Scidac Plus, 2026)
This research is motivated by the problem of education that remains predominantly oriented toward cognitive aspects, resulting in the limited development of students’ potential in spiritual and emotional dimensions. This condition indicates a gap in the implementation of Islamic Religious Education (PAI), which ideally should develop students comprehensively by integrating intellectual, emotional, and spiritual dimensions. Therefore, this study aims to analyze the implementation of holistic management based on spiritual intelligence (SQ), emotional intelligence (EQ), and intellectual intelligence (IQ) in Islamic Religious Education. This study employs a qualitative approach using library research. Data were collected from relevant books, scholarly articles, research reports, and other academic literature and analyzed descriptively and analytically to identify concepts, principles, and strategies related to holistic management in PAI. The findings indicate that holistic management can be implemented through the integration of SQ, EQ, and IQ at the stages of planning, organizing, implementing, and evaluating learning. Such integration enables PAI to move beyond cognitive achievement toward the comprehensive development of students’ character and competencies. The implementation of holistic management contributes to strengthening students’ religious awareness, emotional maturity, critical thinking skills, and ability to apply Islamic values in everyday life. Thus, holistic management provides a more meaningful, contextual, and integrated approach to PAI learning.